2019
DOI: 10.1055/a-0938-2777
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of the endoscopic pressure study integrated system (EPSIS): a novel diagnostic tool for gastroesophageal reflux disease

Abstract: Background The endoscopic pressure study integrated system (EPSIS) is a prototypic system for monitoring intragastric pressure (IGP) fluctuations that result from opening of the cardia during gastric distension. The performance of EPSIS for the diagnosis of gastroesophageal reflux disease (GERD) was evaluated. Methods A retrospective analysis was conducted of data prospectively collected over a 2-year period from 59 patients who underwent gastroscopy, EPSIS, and 24-hour pH monitoring. Using a dedicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 17 publications
2
36
0
1
Order By: Relevance
“…Two examiners checked the waveform and determined the pattern in all cases. See our previous report10 for more details.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two examiners checked the waveform and determined the pattern in all cases. See our previous report10 for more details.…”
Section: Methodsmentioning
confidence: 99%
“…Multivariable logistic regression models were employed to identify clinical, endoscopic, and EPSIS predictors of erosive esophagitis and BE. We defined “EPSIS positivity” as IGP‐max ≤ 18.7 mmHg and a flat pattern to maximize specificity as previously reported 10. Clinically relevant variables with a P value < 0.1 in the univariate analysis were included in the multivariate logistic regression analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…During endoscopic diagnosis, insufflation and deaeration are important not only for finding lesions of the gastrointestinal tract but also for assessing the depth of cancer. Studies on endoscopic pressure study integrated system 1 and scope holding sign 2 of the lower esophagus revealed that the lower esophageal sphincter is visualized endoscopically by insufflation, and the function can be reflected. Rosette sign 3 in achalasia is considered to be indirectly recognized as the abnormal movement of the esophagus by insufflation and deep inspiration.…”
Section: Figurementioning
confidence: 99%